Repeatability of dental plaque quantitation by light induced fluorescence technology in current, former, and never smokers - Gianluca Conte; Amaliya Amaliya; Shipra Gupta; Rosalia Emma; Stefan Gospodaru; Gheorghe Bordeniuc; Valeriu Fala; Sebastiano Antonio Pacino; Salvatore Urso; Giovanni Zucchelli; Riccardo Polosa (BMC Oral Health, 2023)
Abstract Background The effects of smoking on the accumulation of dental plaque have not been studied in depth. We compared dental plaque quantitation obtained with a novel light induced fluorescence technology among current, former, and never smokers and verified measurements’ repeatability. Methods Dental plaque quantitation was objectively assessed by quantitative light induced fluorescence (QLF) technology on three separate study visits in current, former, and never smokers: baseline (day 0), day 7, day 30. Increase in the fluorescence intensity of at least 30% (ΔR30) and 120% (ΔR120) together with the simple oral hygiene (SOH) scoring were considered for analysis. Results The QLF parameters were highly repeatable in each study group (p < 0.0001, by regression analyses). All QLF parameters showed a significant difference between never smokers and current smokers (p = 0.041 for ΔR30; p = 0.027 for ΔR120; p = 0.04 for SOH). No significant differences were observed between never and former smokers and between current and former smokers except for ΔR120 (p = 0.033). Conclusion Dental plaque measurements by QLF technology were highly reproducible and showed greater plaque formation among current smokers compared to non-smokers. Objective and reproducible quantitation of dental plaque can be a valuable clinical and regulatory science endpoint to investigate the effect of smoking cessation medications, combustion-free tobacco products, and consumer care products on oral health. Clinical relevance There is a need to objectively evaluate the relationship between smoking and plaque build-up as well as maturation. Current smokers demonstrated greater and more mature plaque buildup when compared to never and former smokers. Differences in plaque build-up and maturation between current, former and non-smokers may be utilized as an effective tool for patient motivation, identifying therapeutic end-points, translational research as well as prognostication. Trial Registration The study is a pilot study parts of a larger project with registration ID: NCT04649645. As preliminary study, the pilot study referred into this paper started before the larger study registered in ClinicalTrials.gov.